Rancang Bangun Game Edukasi Interaktif sebagai Media Pembelajaran Mufrodat Bahasa Arab Sekolah Dasar (Studi Kasus: SD Al-Ihsan Islamic School) - Ilham Assidiq; Hidayat Hidayat (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Effective learning requires innovation to enhance student engagement and understanding of the material. This study aims to develop an educational game for learning mufrodat (Arabic vocabulary) for fifth-grade elementary school students using Unity 3D and the Game Development Life Cycle (GDLC) approach. The GDLC method consists of five stages: concept, pre-production, production, testing, and release, ensuring a systematic game development process. The game is designed to provide an interactive and enjoyable learning experience, enabling students to acquire Arabic vocabulary through gameplay activities. Unity 3D was chosen for its ability to create dynamic and interactive game environments. The testing results indicate that the developed educational game is effective in enhancing students’ understanding and retention of Arabic vocabulary, with positive feedback received from both students and teachers. Future development may include the addition of more comprehensive learning features and adaptations for various levels of difficulty.